Analisis Pengendalian Kualitas Produk Cushion di PT. X Menggunakan Metode Fuzzy FMEA - Revi Apriliyas; Saufik Luthfianto (Program Studi Teknik Industri Universitas Setia Budi, 2025)
PT. X is one of the companies engaged in the manufacturing industry, producing rubber part components for use in various manufacturing industries. PT. X records a high number of defective products caused by the suboptimal production processes occurring within the company. One of the products produced at PT. X is the Cushion product, which has become one of the products with the highest number of defects and, of course, causes a deficit for PT. ABC. The purpose of this research is to identify the failure risks occurring in the Cushion product, so that improvements can be made to reduce the defective products generated during the production process. The method often used to help identify the causes of product defects is by using the Fuzzy Failure Mode Effect Analysis (Fuzzy FMEA) method. Fuzzy FMEA has advantages compared to the traditional FMEA method, which allows for a combination and result of RPN values that are less accurate. Based on the FRPN calculation results, the highest value was obtained for the type of failure factor of a broken or abnormal machine, then the repair process was carried out using a repair priority scale that corresponds to the order of failure factors with the highest risk level.